Outcome measurement in functional neurological disorder: a systematic review and recommendations - Pick, Susannah; Anderson, David G; Asadi-Pooya, Ali A; Aybek, Selma; Baslet, Gaston; Bloem, Bastiaan R; Bradley-Westguard, Abigail; Brown, Richard J; Carson, Alan J; Chalder, Trudie; Damianova, Maria; David, Anthony S; et al. (Journal of neurology, neurosurgery and psychiatry, 2020)
ObjectivesWe aimed to identify existing outcome measures for functional neurological disorder (FND), to inform the development of recommendations and to guide future research on FND outcomes.MethodsA systematic review was conducted to identify existing FND-specific outcome measures and the most common measurement domains and measures in previous treatment studies. Searches of Embase, MEDLINE and PsycINFO were conducted between January 1965 and June 2019. The findings were discussed during two international meetings of the FND-Core Outcome Measures group.ResultsFive FND-specific measures were identified—three clinician-rated and two patient-rated—but their measurement properties have not been rigorously evaluated. No single measure was identified for use across the range of FND symptoms in adults. Across randomised controlled trials (k=40) and observational treatment studies (k=40), outcome measures most often assessed core FND symptom change. Other domains measured commonly were additional physical and psychological symptoms, life impact (ie, quality of life, disability and general functioning) and health economics/cost–utility (eg, healthcare resource use and quality-adjusted life years).ConclusionsThere are few well-validated FND-specific outcome measures. Thus, at present, we recommend that existing outcome measures, known to be reliable, valid and responsive in FND or closely related populations, are used to capture key outcome domains. Increased consistency in outcome measurement will facilitate comparison of treatment effects across FND symptom types and treatment modalities. Future work needs to more rigorously validate outcome measures used in this population.